Edukasi Stunting melalui E-Leaflet - Ariani, Dini; Septiani, Hani; Setiawan, Doni (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Stunting is largely influenced by chronic nutritional deficiencies during the first 1,000 days of life, making maternal knowledge and early prevention essential. Health education plays a key role in shaping maternal behavior regarding feeding practices, childcare, and early stimulation. Digital media such as e-leaflets provide an accessible and practical tool for delivering health information, particularly in community-based settings. Objective: This community service program aimed to enhance the knowledge of pregnant women and mothers of toddlers regarding stunting and its prevention through structured health education using lecture methods and e-leaflet media. Method: The program was carried out in collaboration with local midwives and community health volunteers. Activities were delivered in several stages, including preliminary survey, problem analysis, implementation of educational sessions, reporting, and dissemination. The educational intervention consisted of counseling supported by e-leaflets containing key information on stunting, its causes, impacts, and preventive strategies. The target participants were pregnant women and mothers of toddlers, selected based on the needs identified in the area. Result: The activity took place on September 12, 2023, at Posyandu Munjul 1 and involved 28 participants. The session was well-received, with mothers actively engaging in the counseling process. Following the educational intervention, participants demonstrated improved understanding of stunting and appropriate childcare practices. The e-leaflet format was considered helpful in reinforcing the information delivered during the session. Conclusion: Health education using e-leaflets effectively improved maternal knowledge regarding stunting prevention. Strengthening and sustaining similar educational programs is recommended to support long-term improvements in community awareness and child health outcomes.